Pemberdayaan Siswa Dalam Meningkatkan Pengetahuan Tentang Pertolongan Pertama Luka Di Pesantren Ittiba As Sunnah Kampung Holtekamp Kota Jayapura - Dwi Astuti; Hendry Kiswanto Mendrofa; Elisabet Bre Boli; Oktliana Pasangka (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Students are an active age group, curious and trying many new things, most of the time students spend on school activities, so students have a high risk of experiencing injury in the school environment.Some pesantren are not only schools, but also provide dormitories so that the pesantren students live and can spend 24 hours doing activities in the pesantren area. Islamic boarding schools have characteristics in spiritual empowerment and also in empowering life skills (life skills). Therefore, it is important to empower Islamic boarding school students in increasing knowledge about wound first aid. The purpose of this dedication is:improve the knowledge and skills of Islamic boarding school students in providing first aid and wound care.The methods used in this service are lectures and demonstrations using slideshow media and brochures. Partners in this service are students of the Ittiba As Sunnah Islamic Boarding School, Holtekamp Village, Jayapura City. The result of this service is that participants understand the material presented so thatthe level of students' knowledge about first aid and wound care increased to 97% of students who had a good level of knowledge, 3% of students had sufficient knowledge, and no students had less knowledge.